D.H. Lawrence: Lawrentian politics and ideology - Skelton, Philip (2002)
This thesis aims to provide a critical re-evaluation of politics and ideology in the work of D.H. Lawrence. The thesis brings a number of authors (including the Marquis de Sade, Robert Louis Stevenson, H. G. Wells and Raymond Chandler) into dialogue with Lawrence - fIrstly in order to interrogate Lawrentian assumptions, but also to relocate a writer often seen as being eccentric to literary circles and to society generally.